DYNAMIC CHARACTERISTICS OF ROTOR-BEARING SYSTEM AND EVOLUTION OF BEARING WEAR (MT) - WEI Lai; HOU XiangLin; ZHANG Yu; FU XueYan (Jixie qiangdu)
Taking the rotor system supported by angular contact ball bearing as the research object, the dynamic model of rotor bearing system is established by using Lagrange equation. Based on the Archard wear model, the calculation model of wear depth of bearing raceways considering lubrication effects is presented. The wear depth is introduced into the system dynamics model as the bearing clearance. The dynamic characteristics of rotor-bearing system and the evolution of bearing wear are carefully analyzed taking into account the rotor speed, bearing preload and disc position. The results show that the influence of bearing wear on dynamic characteristics of rotor-bearing system is closely related to rotor speed and bearing preload. Changing disc position does not lead to the significant variation of dynamic characteristics of rotor-bearing system with wear depth of bearing raceways. The rotor speed significantly affects the bearing wear, the bearing preload has very limited effect on bearing wear, and the variation of the disc position results in the weak difference of wear depth of bearings.